Wall Painting of Pujari Math of Bhaktapur: An Exploration - Dulal, Lok Nath (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Historical evidences prove that painting is considered as the mother of all other forms of art and crafts. While artists start to sculpture the icon and any art objects, very first, they sketch the drawing of concerning deities and specimens, therefore, a painting is said to be the mother of all other sculpture arts. Therefore, the history of creation of painting is older than other forms of arts. On the basis of creating materials, mediums, instruments, technologies, and nature, painting can be classified into three different forms such as fresco, miniature and painted scroll. This article has analyzed the fresco painting of Pujari Math of Bhaktapur. This is an example of polychrome painting which displays an excellent craftsmanship of the artist. Through the perspectives of religion, culture, social values, art skill and technology this art object is known as the representative fresco paintings of Nepal which reveals the fine handiworks of the artists of the medieval period. In painting where people can observe several secular and religious figures of deities and social events associated with the myths of religious scriptures especially Ramayan and Mahabharata the great epics of Hindu. Despite all its amusing qualities, unfortunately, this painting is still not properly considering as the subject of research and study. It is its academic problem and research gaps as well. Thus, raising the research questions such as what types of paintings are painted on the walls and beams of Pujari Math? Why the painting of Pujari Math is considered wonderful work of art? And what are the major features of the painting of Pujari Math? Likewise, this paper fulfills the certain specific objectives such as to examine the paintings of Pujari Math; to explore the significance of the work of art and to analyze the major features of the fresco paintings. It is qualitative research based on primary data and secondary information. Primary data have been obtained from the field using observation and interview method whereas the required secondary information has been collected from different reliable literatures such as journals, documents, books, published and unpublished relevant reports. Thus, for fulfilling the research gaps and problems this paper has been prepared.